Compressive Strength of Concrete using Fly Ash and Rice Husk Ash: A Review - Joel Sam (Salehan Institute of Higher Education, 2020)
Decreasing our over-reliance on cement as an ingredient in the making of concrete due to its contribution to the CO2 emissions has led to numerous researches been conducted to find suitable replacement for cement in concrete mixes. Materials like fly ash, ground granulated blast furnace slag, silica fume, rice husk ash and metakaolin among others have been identified as materials that can at the very least be used as a replacement for cement in concrete mix. These materials are referred to as supplementary cementitious materials (SCMs). This paper reviewed the work that has been done on the use of fly ash and rice husk ash as partial replacements for concrete, its chemical composition and its effect on the compressive strength of concrete. Charts, tables and figures were employed as tools to study the various chemical compounds of fly ash and rice husk ash. It was seen that depending on how the coal or rice husk was initially processed the percentage of some of the minor compounds like Sodium oxide (Na2O), Titanium oxide (TiO2) and Phosphorus pentoxide (P2O5) were sometimes very low or not recorded as part of the final product. The data on the compressive strength of concrete after fly ash and rice husk ash had been added in percentage increments of 0%, 10%, 20%, 30%, 40%, 50% and 0%, 5%, 7.5%, 10%, 12.5%, 15% respectively analysed over a minimum period of 7 days and a maximum period of 28 days found out that the optimal percentage partial replacement of fly ash and rice husk ash for a strong compressive concrete strength is 30% of fly ash and 7.5% of rice husk ash.